Odpowiedzi

2010-01-10T15:52:08+01:00
P=πr²
a)
P1=πr²
P2=π(1,1r)²=1,21*πr²
P2-P1=0,21*πr²
((P2-P1)/P1)*100%=21%
Odp. O 21%
b)P1=πr²
P2=π(2r)²=4πr²
P2-P1=3πr²
((P2-P1)/P1)*100%=300%
Od. O 300 %
16 4 16
2010-01-10T15:52:43+01:00
A) P=3,14*r^2
P=3,14*(r+10%r)^2=3,14*(1,1r)^2=3,14*1,21*r^2=3,7994r^2

3,7994r^2-3,14*r^2=0,6594r^2

3,14*r^2------100%
0,6594r^2------x%

x=0,6594r^2*100%/3,14*r^2=21%

b) P=3,14*r^2
P=3,14*(2r)^2=3,14*4r^2=12,56*r^2

12,56*r^2-3,14*r^2=9,42*r^2

3,14*r^2----100%
9,42*r^2---x%

x=9,42*r^2*100%/3,14*r^2=300%
4 3 4